Appropriateness of antiplatelet therapy for primary and secondary cardio‐ and cerebrovascular prevention in acutely hospitalized older people. (1st August 2017) - Ardoino, Ilaria; Rossio, Raffaella; Di Blanca, Donnatella; Nobili, Alessandro; Pasina, Luca; Mannucci, Pier Mannuccio; Peyvandi, Flora; Franchi, Carlotta; ,
Abstract : Aims: Antiplatelet therapy is recommended for the secondary prevention of cardio‐ and cerebrovascular disease, but for primary prevention it is advised only in patients at very high risk. With this background, this study aims to assess the appropriateness of antiplatelet therapy in acutely hospitalized older people according to their risk profile. Methods: Data were obtained from the REPOSI register held in Italian and Spanish internal medicine and geriatric wards in 2012 and 2014. Hospitalized patients aged ≥65 assessable at discharge were selected. Appropriateness of the antiplatelet therapy was evaluated according to their primary or secondary cardiovascular prevention profiles. Results: Of 2535 enrolled patients, 2199 were assessable at discharge. Overall 959 (43.6%, 95% CI 41.5–45.7) were prescribed an antiplatelet drug, aspirin being the most frequently chosen. Among patients prescribed for primary prevention, just over half were inappropriately prescribed (52.1%), being mainly overprescribed (155/209 patients, 74.2%). On the other hand, there was also a high rate of inappropriate underprescription in the context of secondary prevention (222/726 patients, 30.6%, 95% CI 27.3–34.0%). Conclusions: This study carried out in acutely hospitalized older people shows a high degree of inappropriate prescription among patients prescribed with antiplatelets for primary prevention, mainly due to overprescription. Further, a large proportion of patients who had had overt cardio‐ or cerebrovascular disease were underprescribed, in spite of the established benefits of antiplatelet drugs in the context of secondary prevention.